A Design and Analysis of Voltage Source Inverters for Renewable Energy Applications - M. Murali; Arulmozhiyal Arulmozhiyal; P Sundaramoorthy (Institute of Advanced Engineering and Science, 2014)
The paper proposes design of voltage source inverters for renewable energy applications such as HEV. The wind and solar are growing energy sources to world this sources to be converted alternating one for grid interfacing. Conventional inverters are electronic thyristor which has some drawbacks. To improve its efficiency and performance MOSFET based inverters using controllers has been designedusing PIC controllers. In this project the hardware details of three phases, 50Hz, 60W, 180 degree conduction mode of VSI output waveforms under various load conditions were presented and discussed. This paper will be a significant contributes for forthcoming development of Hybrid Electric Vehicle (HEV).In which Voltage source inverters is operation is performed in Single PIC microcontroller. http://dx.doi.org/10.11591/telkomnika.v12i12.6893